Hallmarks of Life in Single Cell Contact Mechanics: Outstanding Challenges and Perspectives - Moreno-Flores, Susana (Frontiers in Mechanical Engineering, 2020)
Cell mechanics is a fascinating subject that has witnessed a boost of scientific interest in the most diverse disciplines. Evidence of its biological relevance is continuously mounting, unveiling a real-life scenario ever more intricate and complex, and ever less universal. This review revisits the topic at the same time that appraises routine approaches and the synchronous combination of experimental methodologies to tackle cell mechanics in all its dimensionality and complexity. The focus is placed on cultured mammalian cells and on highly sensitive experimental techniques that rely on contact mechanics, namely scanning-probe and traction force microscopies. The importance of time as key variable in theory and experiment is particularly highlighted, together with the need to unambiguously identify the active and physiological contributions to cell behaviour, and provide suitable mechanisms that dynamically interconnect relevant events, cellular structures and organelles to thoroughly understand the mechanobiology of cells. A special consideration is given to the role of friction and the importance of cell-cell interactions in scaling up the mechanical behaviour from single cells to tissues. The topic is in constant demand of crossdisciplinarity, and in that sense, this review also serves the purpose of bringing the subject nearer to the mechanical physics and engineering community.